The effect of skin surface topography and skin colouration cues on perception of male facial age, health and attractiveness. (6th April 2018) - Fink, B.; Matts, P. J.; Brauckmann, C.; Gundlach, S.
Abstract: Objective: Previous studies investigating the effects of skin surface topography and colouration cues on the perception of female faces reported a differential weighting for the perception of skin topography and colour evenness, where topography was a stronger visual cue for the perception of age, whereas skin colour evenness was a stronger visual cue for the perception of health. We extend these findings in a study of the effect of skin surface topography and colour evenness cues on the perceptions of facial age, health and attractiveness in males. Methods: Facial images of six men (aged 40 to 70 years), selected for co‐expression of lines/wrinkles and discolouration, were manipulated digitally to create eight stimuli, namely, separate removal of these two features (a) on the forehead, (b) in the periorbital area, (c) on the cheeks and (d) across the entire face. Omnibus (within‐face) pairwise combinations, including the original (unmodified) face, were presented to a total of 240 male and female judges, who selected the face they considered younger, healthier and more attractive. Results: Significant effects were detected for facial image choice, in response to skin feature manipulation. The combined removal of skin surface topography resulted in younger age perception compared with that seen with the removal of skin colouration cues, whereas the opposite pattern was found for health preference. No difference was detected for the perception of attractiveness. These perceptual effects were seen particularly on the forehead and cheeks. Removing skin topography cues (but not discolouration) in the periorbital area resulted in higher preferences for all three attributes. Conclusion: Skin surface topography and colouration cues affect the perception of age, health and attractiveness in men's faces. The combined removal of these features on the forehead, cheeks and in the periorbital area results in the most positive assessments. Abstract : We investigated the effect of skin surface topography and colouration cues on the perception of male facial appearance. Skin surface topography and colouration cues have an effect on the perception of age, health and attractiveness in men's faces. The combined removal of these features on the forehead, the cheeks and in the periorbital area results in the most positive assessments.